HUBUNGAN PERSEPI SISWA TENTANG KOMPETENSI PEDAGOGIK GURU MATEMATIKA DAN MOTIVASI BELAJAR DENGAN HASIL BELAJAR MATEMATIKA SISWA KELAS VII SMP N 1 JETISTAHUN PELAJARAN 2013/2014 - Dwi Septi (Universitas Sarjanawiyata Tamansiswa, 2016)
The purpose of this research is to find out the correlation between students perception about pedagogik competence of mathematics teacher and motivation to learn with the results of mathematics learning. This research method applied descriptive of correlation. The population in this research is grade VII SMP N 1 Jetis totaling 181 students, with a sample of 120 students taken by cluster random sampling. Analytical techniques multiple regression analysis with requirment of normality and linierity. Based on the results of the research, R = 0,488, meaning that there was a positive correlation between students perception about pedagogik competence of mathematics teacher and motivation to learn and with the results of mathematics learning. 0,246, meaning that there was a positive correlation between students perception about pedagogik competence of mathematics teacher with the results of mathematics learning. 0,285, meaning that there was a positive correlation between motivation to learn with the results of mathematics learning.